Youth unemployment in old Europe: the polar cases of France and Germany - Cahuc, Pierre; Carcillo, Stéphane; Rinne, Ulf; Zimmermann, Klaus F. (Bonn, 2013)
"France and Germany are two polar cases in the European debate about rising youth unemployment. Similar to what can be observed in Southern European countries, a "lost generation" may arise in France. In stark contrast, youth unemployment has been on continuous decline in Germany for many years, hardly affected by the Great Recession. This paper analyzes the diametrically opposed developments in the two countries to derive policy lessons. As the fundamental differences in youth unemployment are primarily resulting from structural differences in labor policy and in the (vocational) education system, any short-term oriented policies can only have temporary effects. Ultimately, the youth unemployment disease in France and in other European countries has to be cured with structural reforms."